2015
DOI: 10.1021/jacs.5b02651
|View full text |Cite
|
Sign up to set email alerts
|

Solution Growth of Single Crystal Methylammonium Lead Halide Perovskite Nanostructures for Optoelectronic and Photovoltaic Applications

Abstract: Understanding crystal growth and improving material quality is important for improving semiconductors for electronic, optoelectronic, and photovoltaic applications. Amidst the surging interest in solar cells based on hybrid organic-inorganic lead halide perovskites and the exciting progress in device performance, improved understanding and better control of the crystal growth of these perovskites could further boost their optoelectronic and photovoltaic performance. Here, we report new insights on the crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
391
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(416 citation statements)
references
References 63 publications
15
391
0
2
Order By: Relevance
“…[54] Shortly after, this concept was transferred to thin films as well. [13,37,55] Schlipf et al used GISAXS to gain quantitative information on crystal-size distribution in perovskite thin films fabricated by a sequential deposition method. [11,13] They found that starting from a film of crystalline PbI 2 , where the crystals are arranged in a pancake-like stack, the MAI diffuses from the top down through the stack and begins the conversion into the perovskite phase.…”
Section: Two-step (Sequential Deposition)mentioning
confidence: 99%
“…[54] Shortly after, this concept was transferred to thin films as well. [13,37,55] Schlipf et al used GISAXS to gain quantitative information on crystal-size distribution in perovskite thin films fabricated by a sequential deposition method. [11,13] They found that starting from a film of crystalline PbI 2 , where the crystals are arranged in a pancake-like stack, the MAI diffuses from the top down through the stack and begins the conversion into the perovskite phase.…”
Section: Two-step (Sequential Deposition)mentioning
confidence: 99%
“…Dissolutionrecrystallization growth methods resulting in fi lm formation have been shown to depend on both hydration and formation of intermediate complexes. [ 15,32 ] The polar and aprotic, and thus hydrophilic characteristics of DMF [ 31 ] are possibly being emulated in the fast evaporation of EtOH while AcOH assists in complexing to form the correct intermediate phase for perovskite formation.…”
Section: Pinhole-free Perovskite Layersmentioning
confidence: 99%
“…[46,47] While the first process is constrained mainly to the bulk of the film where concentration of MAI is low due to being limited by diffusion and the structure from PbI 2 is mostly preserved, the latter process occurs closer to the film surface where the high iodide concentration leads to partial dissolution of the PbI 2 layer and subsequently forms crystals in (002) orientation. This process is reminiscent of what happens in the spin-coating/interdiffusion method where the MAI concentration is higher.…”
Section: Research Newsmentioning
confidence: 99%